All Days 2013
DOI: 10.2523/iptc-17168-ms
|View full text |Cite
|
Sign up to set email alerts
|

Variable Nozzle-Based Inflow Control Device Completion: Inflow Distribution Comparison, Analysis, and Evaluation

Abstract: This paper presents a study of horizontal well completions equipped with inflow control devices (ICDs) in a large, unconsolidated sandstone reservoir in Saudi Arabia. The focus is the improved production performance gained through a completion using ICDs with variable nozzle settings across the openhole section vs. that from a cemented, perforated liner completion and uniform nozzle setting ICD completion performance. Discussion includes an overview of ICD and intelligent completions and their components, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…They said that these tools are often installed along the entire length of a horizontal well with the logic that because choking level is proportional to flow, the tool will automatically produce a more uniform flow profile. Abd Elfattah et al (2013) indicated that there are various types of ICDs which are tube, helical, orifice and nozzle types. Figure 2 shows a typical representation of the essential parts in an inflow control device; the screen, the housing and the nozzle where the fluid makes entrance into the completion Li et al (2011) said that the pressure drop created by ICD is considered impairment to the productivity of wells.…”
Section: Introductionmentioning
confidence: 99%
“…They said that these tools are often installed along the entire length of a horizontal well with the logic that because choking level is proportional to flow, the tool will automatically produce a more uniform flow profile. Abd Elfattah et al (2013) indicated that there are various types of ICDs which are tube, helical, orifice and nozzle types. Figure 2 shows a typical representation of the essential parts in an inflow control device; the screen, the housing and the nozzle where the fluid makes entrance into the completion Li et al (2011) said that the pressure drop created by ICD is considered impairment to the productivity of wells.…”
Section: Introductionmentioning
confidence: 99%